THE ROLE OF HUMAN RESOURCE TRAINING AND DEVELOPMENT IN IMPROVING THE QUALITY OF PUBLIC SERVICES IN BANDUNG CITY - Ade Mubarok (CV. Radja Publika, 2021)
This study examines the role of human resource training and development in improving the quality of public services in Bandung City. Public service quality is an important indicator in measuring the effectiveness of local government performance. In the era of digital transformation and bureaucratic reform, government employees are expected to possess adequate competencies, professionalism, and responsiveness in serving the community. This research uses a qualitative descriptive method through literature study and analysis of secondary data obtained from journals, government reports, and regulations related to public service and human resource development. The findings indicate that training and development programs contribute significantly to improving employee competence, work discipline, communication skills, and service efficiency. Furthermore, the implementation of competency-based training supports the realization of transparent, accountable, and citizen-oriented public services. However, several challenges remain, including unequal training opportunities, limited budgets, and resistance to organizational change. Therefore, the Bandung City Government needs to strengthen sustainable human resource development policies to achieve optimal public service performance.